School-based mental health promotion in children and adolescents with StresSOS using online or face-to-face interventions: study protocol for a randomized controlled trial within the ProHEAD Consortium - Eschenbeck, Heike; Bauer, Stephanie; Kaess, Michael; Moessner, Markus; Salize, Hans Joachim (BioMed Central, 2019)
Abstract Background Schools are an ideal setting in which to promote health. However, empirical data on the effectiveness of school-based mental health promotion programs are rare, and research on universal Internet-based prevention in schools is almost non-existent. Following the life skills approach, stress management training is an important component of health promotion. Mental health literacy is also associated with mental health status, and it facilitates formal help-seeking by children and adolescents (C&A). The main objectives of this study are (1) the development and evaluation of an Internet-based version of a universal school-based health promotion program called StresSOS and (2) demonstrating non-inferiority of the online setting compared to the face-to-face setting. StresSOS aims to improve stress management and mental health literacy in C&A. Methods/design A school-based sample of 15,000 C&A (grades 6–13 and older than 12 years) will be recruited in five regions of Germany within the ProHEAD Consortium. Those with a screening result at baseline indicating no mental health problems will be invited to participate in a randomized controlled trial comparing StresSOS online to an active online control condition (Study A). In addition, 420 adolescents recruited as a separate school-based sample will participate in the StresSOS face-to-face intervention. Participants in both intervention groups (online or face-to-face) will receive the same eight treatment modules to allow for the comparison of both methods of delivery (Study B). The primary outcome is the number of C&A with symptoms of mental health problems at a 12 months follow-up. Secondary outcomes are related to stress/coping (i.e., knowledge, symptoms of stress, coping resources), mental health literacy (knowledge and attitudes toward mental disorders and help-seeking), program usage patterns, cost-effectiveness, and acceptability of the intervention. Discussion This study represents the first adequately powered non-inferiority trial in the area of school-based mental health promotion. If online StresSOS proves efficacious and non-inferior to face-to-face delivery, this offers great potential for health promotion in youths, both in and outside the school environment. Trial registration German Clinical Trials Register, DRKS00014693 . Registered on 14 May 2018.
In: Trials, 20 (2019), Nr. 64. pp. 1-12. ISSN 1468-6694